Entrepreneurialism and society : new theoretical perspectives - Eberhart, Robert N.; Lounsbury, Michael; Aldrich, Howard (Emerald Publishing Limited, 2022)
The first of two volumes bringing together researchers from an array of disciplines including sociology, organization theory, strategy, and organizational behaviour, Entrepreneurialism and Society: New Theoretical Perspectives addresses the question of how entrepreneurship has transformed from an organizing activity into an ideology that is changing society. The authors investigate the transformation of entrepreneurship into a social phenomenon, leading to an understanding of how entrepreneurship is shaping the acceptance of inequality, new employment relationships, changed understandings of social outcomes, altered policies, and social precarity. Examining the role of organizations in society, Entrepreneurialism and Society invigorates academic research by developing new perspectives on how entrepreneurs and their organizations shape our social world.
Keywords: Entrepreneurship -- Social aspects.; Business & Economics -- Entrepreneurship.; Entrepreneurship.; elektronické knihy; electronic books